The role of TQM requirements in promoting social responsibility perspectives - Khenchour, djamel; Djemaa, KHIREDDINE (Milev Journal of Research and Studies, 2022)
The aim of this study is to understand the role of TQM requirements in promoting social responsibility perspectives, as the philosophy of TQM aims to continuously improve in all aspects. Institutions wishing to continue and succeed must interact with society by adopting social responsibility within their objectives The study found that there is a role for the requirements of TQM (senior management commitment, customer focus, continuous improvement, teamwork) in establishing social responsibility perspectives.